In-depth characterization of phytase-producing plant growth promotion bacteria isolated in alpine grassland of Qinghai-Tibetan Plateau - Li, Qi; Yang, Xiaolei; Li, Jianhong; Li, Mingyuan; Li, Changning; Yao, Tuo (Frontiers in Microbiology, 2023)
The use of plant growth promoting bacteria (PGPB) express phytase (myo-inositol hexakisphosphate phosphohydrolase) capable of hydrolyzing inositol phosphate in soil was a sustainable approach to supply available phosphorus (P) to plants. In this study, a total of 73 bacterial isolates with extracellular phytase activity were selected from seven dominant grass species rhizosphere in alpine grassland of Qinghai-Tibetan Plateau, and these bacteria as members of phyla Proteobacteria (90.41%) and Actinobacteria (9.59%) were related to 16 different genera. The isolates of Pseudomonas species showed the highest number (36) and average values of phytase activity (0.267 ± 0.012 U mL-1), and isolated in all plants. Then, plant growth promoting (PGP) traits of Pseudomonas species were studied by qualitative and quantitative methods including organic (egg yolk lecithin)/inorganic (tricalcium phosphate) P solubilization, plant hormones (PHs) (trans-Zeatin, t-Z; gibberellin acid, GA3; indoleacetic-3-acid, IAA) production, nitrogen fixation, 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity and antimicrobial activity. Our results indicated that the isolates of Pseudomonas was the a great candidate for PGPBs which showed a multiple of PGP traits. In addition, six strains were positive in phytase gene (β-propeller phytase, bpp) amplification. Further experiment suggested their growth promoting effect on Lolium perenne L., which significantly increased the shoot length, shoot/root fresh weight, root average diameter and root system phytase activity under P-limitation, and the expression of phytase gene (bppP) in root system were verified by qPCR. Then, the PHY101 gene encoding phytase from P. mandelii GS10-4 was cloned, sequenced, and recombinant expression in Escherichia coli. Biochemical characterization demonstrated that the recombinant phytase PHY101 revealed the highest activity at pH 6 and 40℃ temperature. In particular, more than 60% of activity was retained at a low temperature of 15℃. This study demonstrates the opportunity for commercialization of the phytase-producing PGPB to developing localized microbial inoculants and engineering rhizobacteria for sustainable use in alpine grasslands.